Habitat manipulation for sustainable management of Philaenus spumarius, the main vector of Xylella fastidiosa in Europe. Issue 10 (5th July 2022) - Morente, Marina; Ramírez, Marcos; Lago, Clara; de las Heras‐Bravo, Daniel; Benito, Alejandro; Moreno, Aránzazu; Fereres, Alberto
Abstract: Background: The unexpected Xylella fastidiosa ( Xf ) outbreak in Europe has led to aggressive management of the disease in recent years. As there is no cure for infected plants, management of vector populations is mandatory to contain the spread of Xf in infected areas. We aimed to assess the suitability of plant species commonly used as cover crops for the population growth of Philaenus spumarius L. (Aphrophoridae) . Thus, we conducted a series of no‐choice and multiple‐choice assays to assess the oviposition preference of P. spumarius adults as well as the development and mortality rate of nymphs on 10 candidate plant species under laboratory and semi‐field conditions. Our results will help to design ecological infrastructures, including a pull‐push strategy for effective management of Xf vectors in olive groves. Results: Results showed that Anthriscus cerefolium is a suitable plant to enhance oviposition but has a lethal effect on the first nymphal instars of P. spumarius . Moreover, Diplotaxis tenuifolia is not suitable for oviposition or nymphal development. Sinapis alba does not enhance oviposition but is suitable for nymphal development with a medium‐high cumulative mortality of the nymphs. Conversely, adults and nymphs had a high preference and low mortality on Taraxacum officinale, and nymphs showed a medium‐high preference on Lavandula angustifolia, suggesting that these two species should be avoided as ground cover plants on Xf ‐susceptible crops. Conclusion: The results obtained in our study open new ways to manage the vectors of Xf by using specific plant species as ground cover, which in turn will reduce the spread and prevalence of Xf . © 2022 Society of Chemical Industry. Abstract : The arrangement of Diplotaxis tenuifolia (repellent), Anthiscus cerefolium (lethal) and Sinapis alba (attractive) under a push‐pull strategy in olive groves is a promising alternative for sustainable control Philaenus spumarius populations.